Disrupted rich club network in behavioral variant frontotemporal dementia and early‐onset Alzheimer's disease. Issue 3 (17th December 2015) - Daianu, Madelaine; Mezher, Adam; Mendez, Mario F.; Jahanshad, Neda; Jimenez, Elvira E.; Thompson, Paul M.
Abstract: In network analysis, the so‐called "rich club" describes the core areas of the brain that are more densely interconnected among themselves than expected by chance, and has been identified as a fundamental aspect of the human brain connectome. This is the first in‐depth diffusion imaging study to investigate the rich club along with other organizational changes in the brain's anatomical network in behavioral frontotemporal dementia (bvFTD), and a matched cohort with early‐onset Alzheimer's disease (EOAD). Our study sheds light on how bvFTD and EOAD affect connectivity of white matter fiber pathways in the brain, revealing differences and commonalities in the connectome among the dementias. To analyze the breakdown in connectivity, we studied three groups: 20 bvFTD, 23 EOAD, and 37 healthy elderly controls. All participants were scanned with diffusion‐weighted magnetic resonance imaging (MRI), and based on whole‐brain probabilistic tractography and cortical parcellations, we analyzed the rich club of the brain's connectivity network. This revealed distinct patterns of disruption in both forms of dementia. In the connectome, we detected less disruption overall in EOAD than in bvFTD [false discovery rate (FDR) critical P perm = 5.7 × 10 −3, 10, 000 permutations], with more involvement of richly interconnected areas of the brain (chi‐squared P = 1.4 × 10 −4 )—predominantly posterior cognitive alterations. In bvFTD, we found a greater spread of disruption including the rich club (FDR critical P perm = 6 × 10 −4 ), but especially more peripheral alterations (chi‐squared P = 6.5 × 10 −3 ), particularly in medial frontal areas of the brain, in line with the known behavioral socioemotional deficits seen in these patients. Hum Brain Mapp 37:868–883, 2016 . © 2015 The Authors. Human Brain Mapping Published by Wiley Periodicals, Inc .